Analisis Kinerja Tenaga Kependidikan Akademik terhadap Kepuasan Mahasiswa : Studi Kasus Perguruan Tinggi di Kabupaten Garut - Kurnaeli K; Intan Tenisia Prawita Sari (Fakultas Ekonomi Universitas Garut, 2018)
Student satisfaction to academic division of university can be achieved by a good and optimal service performance of academic division. The object of the research is Higher education students in Garut Regency. The Purpose of the research is to find out how performance of Higher education institution’s academic division in Garut Regency.Is this performance has satisfying students as a consumer or not. If not, what factor that influenced. Based on conceptual framework, hypothetical has been made that is academic division performance influence to student satisfactory in their own university. Analytical methods that used is descriptive analytics for respondent responses and path analytic for influence. Validity and reability test is used for reseach instrument, and Successive Interval Methods is used to change data from ordinal to interval data. Based on founding and discussion can concluded respondent based on gender are quiet balance and the most experienced on academic service is 3 years (6 semester). Tangible, realibility, responsiveness, assurance, and empathy variables both together and partial is influence on consument satisfaction. Then, reability variables is the one who dominated influence on consument satisfactory.